Handling Of Umrah Packages In Kedah: An Early Review - Muhamad Amar Mahmad; Nor Hanani Ismail; Khadafi Hj Rofie; Shukri Ahmad; Abdel Rahman Ibrahim Suleiman Islieh (Tianjin University, 2024)
Journal of Tianjin University Science and Technology Volume 54 Issue 12 Page (1-9)